An Investigation Into Students’ Approaches To Learning in Higher Education - Abdelbasit Gadour; Samia Amniana (BIRCU, 2013)
This study explored students’ approaches to learning in higher education with the aim of identifying the strategies and study skills that students believe lead to effective learning. A qualitative method, in the form of semi-structured interviews, was used with ten students from Newcastle University, five of whom were postgraduates. The study revealed a strong relationship between students’ approaches to learning and the study skills they use. Additionally, the study indicated that mature students (postgraduates) tend to have a more effective approach to learning than younger students (undergraduates). The implications of this study highlight the importance of having organised strategies for effective learning in higher education and achieving positive outcomes.